SYSTEM AND METHOD FOR INTERACTIVE VISUAL EFFECTS COMPOSITING (2006)
There is provided a system for acquiring video data and audio data. In an exemplary embodiment, the system comprises a camera that is adapted to acquire video data suitable for recording on a tangible medium, the video data being representative of an image of a subject taken at an azimuth value relative to the subject, a microphone that is adapted to acquire audio data that corresponds to the video data on the tangible medium, the microphone being adapted to acquire the audio data from the azimuth value relative to the subject, and a compass that is adapted to provide data corresponding to the azimuth data, the azimuth data being stored along with the corresponding video data and audio data on the tangible medium.